Influence of erotic television films on adolescent students’ attitude towards people living with HIV and Aids (2014)
The Acquired Immunodeficiency Syndrome (AIDS), with its human and material losses, has continued to pose great health challenges to vulnerable human population groups. The factors driving the exacerbation of the pandemic are persisting, especially among the adolescent cohort in part due to widespread discrimination and stigmatization of people living with HIV/AIDS. Previous studies have shown that exposure to mass media could influence attitude and behaviour. This knowledge notwithstanding, empirical data examining the relationship between exposure to erotic television films and adolescents’ attitude towards people living with HIV/AIDS are rare. This study, carried out in Ibadan, Nigeria, investigated the influence of erotic television films on attitude of adolescent students towards people living with HIV/AIDS. The study employed ex-post facto and Focus Group Discussion (FGD) research methods. Systematic sampling method was employed in selecting a total oj 800 adolescents between the ages of 14 and 18 years from secondary and tertiary institutions, who responded to the questionnaire while purposive sampling technique was used in selecting 64 discussants who took part in the FGD. The data collected were analysed using descriptive statistics and One- Way ANOVA. Exposure to erotic television films showed a significant relationship with adolescent students’ attitude towards people living with HTV/AIDS (p<0.05). Scheffe post-hoc analysis showed that increased exposure to erotic television films is associated with less empathy towards people living with HIV/AIDS. The result of the FGD revealed that a little above half of the discussants (52.5%) believed that people tend to show less empathy towards people living with HIV/AIDS because they lack correct information about the disease. With high media diet among the adolescent cohort, broadcast regulatory agencies need to establish stringent ethical measures in ensuring that factual information about the disease is embedded in such films. Intervention programmes embarked upon by Government and Non- Governmental Organizations should aim at reducing adolescents’ feeling of apathy towards people living with HTV/AIDS.